Industrial water treatment process technology - Pal, Parimal (Butterworth-Heinemann, 2017)
Industrial Water Treatment Process Technology begins with a brief overview of the challenges in water resource management, covering issues of plenty and scarcity-spatial variation, as well as water quality standards. In this book, the author includes a clear and rigorous exposition of the various water resource management approaches such as: separation and purification (end of discharge pipe), zero discharge approach (green process development), flow management approach, and preservation and control approach. This coverage is followed by deeper discussion of individual technologies and their applications